Beispiel Nr: 05
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 1 x +2 + 3 z=4\\ 2 x +3 y + 2 z=6\\ 0 x +2 y + 6 z=0\\ \\ \\ \textbf{Rechnung:} \\\small \begin{array}{l} x+2y+3z=4 \\ 2x+3y+2z=6 \\ 2y+6z=0 \\ \\ \end{array} \qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline1 & 2 & 3 & 4 \\ 2 & 3 & 2 & 6 \\ 0 & 2 & 6 & 0 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}2=\text{Zeile}2\cdot 1\text{-Zeile}1\cdot 2 \\z2s1=2\cdot 1-1\cdot 2 =0 \\ z2s2=3\cdot 1-2\cdot 2 =-1 \\ z2s3=2\cdot 1-3\cdot 2 =-4 \\ z2s4=6\cdot 1-4\cdot 2 =-2 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline1 & 2 & 3 & 4 \\ 0 & -1 & -4 & -2 \\ 0 & 2 & 6 & 0 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}3=\text{Zeile}3\cdot (-1)\text{-Zeile}2\cdot 2 \\z3s2=2\cdot -1-(-1)\cdot 2 =0 \\ z3s3=6\cdot -1-(-4)\cdot 2 =2 \\ z3s4=0\cdot -1-(-2)\cdot 2 =4 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline1 & 2 & 3 & 4 \\ 0 & -1 & -4 & -2 \\ 0 & 0 & 2 & 4 \\ \end{array} \\ \\ z=\frac{4}{2}=2\\y \cdot (-1)+(-4)\cdot2=(-2)\\y= -6\\x\cdot 1+2\cdot-6+3\cdot2=4\\x= 10\\L=\{10/-6/2\}$